Uji Toksisitas Akut Asam Askorbat Per Oral pada Organ Ginjal dan Hepar Tikus (Rattusnorvegicus) Betina Galur Wistar - Saraswati, Ni Made Ayu; Indrayan, Agung Wiwiek; Mahendra, Agung Nova; Sumardika, Wayan (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effects of acute toxicity of ascorbic acid on the kidney and liver organs of female Wistar rats. The method used in this study is an experimental method with a post-test only control group design model approach. The results showed that the average SGPT level was 61.24 ± 9.416 U / L. While the results of the mean value of blood serum creatinine levels were (1.48) (0.60 - 2.00) Based on bivariate analysis, there was no significant difference in the mean between the treatment and control groups (P <0.001). Acute administration of ascorbic acid at a dose of 9 mg / 200 grams of BW / day, 36 mg / 200 grams of BW / day, 72 mg / 200 grams of BW / day did not increase SGPT and blood creatinine levels in female Wistar rats. The results obtained using doses of 9 mg, 36 mg, 72 mg on toxicity were not too significant for the kidney and liver organs. Administration of ascorbic acid has an impact on SGPT (Serum Glutamic Pyruvic Transaminase) levels in the liver of mice. Doses of 9 mg, 36 mg, and 72 mg of ascorbic acid did not show significant toxicity effects on the kidneys and livers of mice. Keywords: Ascorbic Acid, Creatinin Serum, SGPT.